An Exegesis Paper On Ignatius To Ephesians 18-19 - Philip Suciadi Chia; Juanda Juanda (Theological Journal Kerugma, 2020)
There are 7 letters written by Ignatius from Antioch, while traveling to Rome. One of them is the church at Ephesus which consists of 21 chapters. In this letter, Ignatius urges these Christians to be in unity with their bishop, because the Docetists were denying the true humanity of Christ. We also find here the unique emphasis on Jesus Christ as the one physician and the Eucharist as ‘the medicine of immortality’. Furthermore, by insisting on the virgin birth to explain Jesus’ existence as the Christ, Ignatius makes a vigorous anti-docetic statement. In this exegetical study, the writer will specifically examine only chapters 18-19, to find the meaning of the writing of these two chapters, which are related to suffering through self-sacrifice. Ignatius speaks in self-deprecating terms as he gives his life as a self-offering. By the world, he is regarded as a criminal but in God’s plan of salvation (oikonomia) his sufferings benefit the church. Ignatius merely makes this more explicit with his remark that what God had prepared ‘had its beginning’. He probably would have gone on to stress the passion as the culmination of God’s plan, though he was also conscious of the fact that Satan’s power had not even yet been completely destroyed.